Prescribing pattern of antihypertensive drugs in diabetic patients of Southern Province, Kingdom of Saudi Arabia - Shaik Alavudeen, Sirajudeen; Mohammed Alakhali, Khaled; Mohammad Asif Ansari, Shaik; Abdulla Khan, Noohu (Ars Pharmaceutica (Internet), 2015)
Background. Hypertension is extremely prevalent in patients with diabetes. Limited data exist on utilizationpatterns of antihypertensive in this population are consistent with evidence-based practice guidelines. Objective. To evaluate utilization patterns of antihypertensive agents among diabetic patients with hypertension. Design. Retrospective descriptive cross sectional. Patients / Participants. 149 patients with diabetes and hypertension from outpatient department at FamilyMedicine Hospital, Ahaderfieda. Khamis Mushait, K.S.A. Results. Over 43% of patients were receiving calcium channel blockers (CCB), 36.2 % of received angiotensinconverting enzyme inhibitors (ACEI), followed by angiotensin receptor blockers (ARBs) (34.9%),diuretics (34.2%) and β -blockers (16.2%). Patients on monotherapy were mostly receiving CCB (34.3%)and ACEI (29.9%). The majority (55.03%) of treated patients were on multidrug regimens. In patientswith coronary artery disease (CAD), a diuretic with ACEI (25%) and calcium channel blocker with angiotensinreceptor blocker (25%) was most commonly prescribed. Conclusions. Patterns of antihypertensive therapy were generally consistent with international guidelines.Areas of improvement include increasing ACEI/ARB and diuretic use, decreasing the number ofuntreated patients, and increasing the proportion of patients with controlled BP in this population.